Indirect interactions between climate and cropland distribution shape fire size in West African grasslands - Schulte to Bühne, Henrike; Tobias, Joseph A.; Durant, Sarah M.; Pettorelli, Nathalie (Landscape ecology, 2023)
Context Climate and land use changes often interact, yet our ability to predict their combined effects on biodiversity is currently limited. In particular, the combined effects of climate and land use on key ecosystem dynamics, such as disturbance regimes, that shape biodiversity across large spatial scales, are poorly understood. Objectives We assess how indirect climate–land use interactions influence disturbance regimes by examining the mechanistic pathways by which climate and proximity to cropland interact to shape fire size in a West African grassland ecosystem, the W-Arly-Pendjari transboundary protected area complex. Methods We use remotely sensed indicators of burned area, rainfall, cropland distribution, and vegetation dynamics to test two spatially explicit hypotheses about the interaction between climate and land use effects on fire dynamics. Results We demonstrate that in areas where wet season grass production (which is driven by rainfall) is higher, fires are larger, but that this relationship depends on the distance to cropland. Close to cropland, environmental drivers of fire size (wet season grass production, and progressive loss of fire fuel during the fire season) have little effect on fire size, as fuel breaks induced by cropland limit fire size. Conclusion Our results suggest that the extent to which climate factors control fire dynamics in this African grassland depends on the spatial distribution of land use. More broadly, considering the relative spatial distributions of interacting stressors may be key to improving predictions of their combined impacts on ecosystem functioning.